2019
DOI: 10.1108/f-12-2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

How can universities align bricks with modern learning?

Abstract: Purpose This study aims to explore modern learning (ML) scenarios in Dutch higher education towards 2030 and corresponding consequences for facility management (FM) and corporate real estate strategies (CRES) of universities of applied sciences (UAS). Design/methodology/approach The designing an accommodation strategy model is used to retrieve the match between demand and supply in real estate of Dutch UAS for both present and future. Application of this model resulted in a scenario-planning session with six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Out of the 57 respondents who manage their buildings in-house, 53 (93%) are engaged in activities that are property management related, whereas the remaining 6% (3 owners) are into core competencies that do not relate to property management. The findings made concerning the impact of core competencies on the choice of FM strategy concur with previous findings of Adhikari et al (2019), Van Sprang et al (2019); Toe (2015); Olusegun et al (2015); Amos and Gadzekpo (2016); Kroes and Ghosh (2010); Ikediashi et al (2015), Ikediashi (2014) and Tannor et al (2021). In a recent study on FM in shopping malls in Ghana, Tannor et al (2021) found that 90% most of the shopping mall owners outsourced FM because they were into activities that do not relate to FM and wanted to focus on their core competencies.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Out of the 57 respondents who manage their buildings in-house, 53 (93%) are engaged in activities that are property management related, whereas the remaining 6% (3 owners) are into core competencies that do not relate to property management. The findings made concerning the impact of core competencies on the choice of FM strategy concur with previous findings of Adhikari et al (2019), Van Sprang et al (2019); Toe (2015); Olusegun et al (2015); Amos and Gadzekpo (2016); Kroes and Ghosh (2010); Ikediashi et al (2015), Ikediashi (2014) and Tannor et al (2021). In a recent study on FM in shopping malls in Ghana, Tannor et al (2021) found that 90% most of the shopping mall owners outsourced FM because they were into activities that do not relate to FM and wanted to focus on their core competencies.…”
Section: Resultssupporting
confidence: 91%
“…Prior to this study, Holmén et al (2017) found that when construction firms or property developers undertake FM in-house, it offers the strategic advantages of reducing uncertainty and risk associated with owning and operating the property and offers long-term technological quality for customers. There are other studies that have previously associated the in-house strategy with the strategic benefits of risk reduction and profit and flexibility (Ikediashi et al , 2015; Ikediashi, 2014; Amos and Gadzekpo, 2016; Adhikari et al , 2019; Van Sprang et al , 2019). For instance, in Ikediashi et al (2015), the in-house approach to FM was found to be better for certain FM services such as oxygen supply and water supply in hospitals because these services are very essential to health-care delivery and could be a huge risk when not closely monitored by the hospitals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this can also be seen in terms of short-and long-term objectives (Abdullah et al, 2011), whereas management services can be seen as short-term objectives supporting longterm objectives. A viewpoint also shared by Van Sprang et al (2019) and Abdullah et al (2019). Before deciding on how to organise the service, Usher (2004) also points out that there are different pros and cons tied to the decision.…”
Section: Evaluating Screening Schemementioning
confidence: 84%
“…In institutions of higher learning, Amos and Gadzekpo (2016b) and Kroes and Ghosh (2010) found that information technology (IT), cleaning, landscaping and maintenance of buildings and plants are not core competencies of the institutions, thus outsourcing such services to third-party agents who specialize in them offers the principal (educational institutions) the strategic advantage of remaining focused on their core competencies of education. Other authors such as Van Sprang et al (2019) and Amos and Gadzekpo (2016a, 2016b) provided a different dimension to the strategic advantages of outsourcing by suggesting that it offers the principal the flexibility to enter short-term FM contracts that can be terminated once the service delivery is complete. In some literature, the strategic advantages that come with engaging an agent to provide FM services were said to have the potential to increase productivity and operational capabilities of the principal as well as satisfaction for its users because of the quality of FM services that are undertaken by the expert agent (Tannor et al , 2022b; Agburu et al , 2017; Amos and Gadzekpo, 2016a, 2016b).…”
Section: Literature Reviewmentioning
confidence: 99%